2016
DOI: 10.5935/abc.20160025
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia is Associated with Unfit and Overweight-Obese Children and Adolescents

Abstract: BackgroundBoth poor aerobic fitness and obesity, separately, are associated with abnormal lipid profiles.ObjectiveTo identify possible relationships of dyslipidemia with cardiorespiratory fitness and obesity, evaluated together, in children and adolescents.MethodsThis cross-sectional study included 1,243 children and adolescents (563 males and 680 females) between 7 and 17 years of age from 19 schools. Obesity was assessed using body mass index (BMI) measurements, and cardiorespiratory fitness was determined v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 22 publications
2
28
0
5
Order By: Relevance
“…Data showed that inappropriate anthropometric measurements (WHtR and BMI) or excess body fat assessed by bioimpedance were positively associated with higher TC and Non-HDLc values, and negatively so with HDLc, in both boys and girls. This confirmed previous data in which it was observed that overweight/obese children who did not engage in physical activity had higher levels of TC 21 . It is important to stress that in this study, most of the children and adolescents engaged in physical activity at the Knowledge Station itself.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Data showed that inappropriate anthropometric measurements (WHtR and BMI) or excess body fat assessed by bioimpedance were positively associated with higher TC and Non-HDLc values, and negatively so with HDLc, in both boys and girls. This confirmed previous data in which it was observed that overweight/obese children who did not engage in physical activity had higher levels of TC 21 . It is important to stress that in this study, most of the children and adolescents engaged in physical activity at the Knowledge Station itself.…”
Section: Discussionsupporting
confidence: 92%
“…Comparative studies of the association between body composition and plasma lipids between genders are scarce. Most studies only investigate the influence of gender on the distribution of the prevalence of dyslipidemia 21,28 . In our study we investigated not only the prevalence but also the association between different indicators of obesity and blood lipid values.…”
Section: Discussionmentioning
confidence: 99%
“…Obez bireylerde dislipideminin sebebi yağ dokusunun lipolizinden sorumlu bir enzim olan hormon duyarlı lipazın, insülin tarafından inhibe edilmesidir [25]. Brezilya'da 1234 çocuk ve adolesanda yapılan bir çalışmada, lipid bozukluğunun fazla kilolu ve obez çocuklarda daha sık olduğu gösterilmiştir [15]. Bir çalışmada obez çocuklarda kolesterol hariç, belirgin şekilde lipid düzeylerinde bozulma olduğu bildirilmişken [16], morbid obez erişkinlerde yapılan bir başka çalışmada VKİ'nin TG ile pozitif, HDL ile negatif ilişkisi olduğu gösterilmiştir [21].…”
Section: Discussionunclassified
“…Firstly, in combining low physical fitness with indicators of high adiposity, there is an increase in cardiovascular risk in comparison with the separate outcomes. 26,27 Secondly, cardiorespiratory fitness, muscle strength and low adiposity are independently associated with cardiometabolic risk [28][29][30] and thus, it is desirable that young people should fulfill all of these health criteria. Thus, the results showed that engagement in physical education classes was associated with higher probability of achievement of combined health criteria among participants who were not sports practitioners.…”
Section: Discussionmentioning
confidence: 99%